Persepsi Masyarakat terhadap Kinerja Pemerintahan Desa di Desa Medan Estate - Dipo Piswatama; Julia Ivanna (Public Service and Governance Journal, 2024)
Community perception of the performance of village government in Medan Estate village means that the author focuses the research in this article on looking at the extent of the performance of village government in Medan Estate village. The aim of this research is to determine the performance of village government in Medan Estate village. This type of research is qualitative. Qualitative research methods focus on interviewing other people in external and complex environments. (Moleong, 1999; Creswell, 2002, Lindloft, 1995), states that qualitative research methods are more inductive. This means that the research step that must be prioritized is data based on facts, symptoms, phenomena, reality which is the theme, then processed, processed, so that at the end of the research it can become a proposition, model or even theory. The solution to this problem is that the president must have supervisors in the village government such as the TNI, police and PPKn lecturer experts to select which members of the village apparatus are not suitable for use or use. And this aims to ensure that people who are on the inside route are not worthy of getting a job, must be smart, wise, competent people who are worthy of being village officials. And the results of village government performance are increasingly advanced and evenly distributed.